Privacy‐protected communication for location‐based services. Issue 2 (11th May 2011) - Werner, Martin
Abstract: Location‐based services (LBSs) are emerging fast, and the problems with privacy are growing with them. Although a platform for LBSs can provide the user with high‐quality LBS browsing and powerful mechanisms to reduce the amount of location data transmitted, such a platform is dangerous because it has to manage the location data of the users and the actual service use. This aggregation of private data is a risk in itself. With this paper, we want to show that it is possible to implement most LBSs without such a platform and propose a mechanism enabling fine‐grained control of privacy for an LBS user. We make use of strong cryptographic techniques to enable a real trust relation between individuals and a weaker trust relation between an individual and a company. Copyright © 2011 John Wiley & Sons, Ltd. Abstract : With this paper, we present a novel framework for message exchange in location‐based services removing the need for a central trusted third party. In addition, we show, that this approach can be used to realize an "attestation of origin" feature allowing for better value‐added services. Furthermore, we show how to apply this generic setup for the realization of a privacy‐aware online social network.